Establishing diversity, equity, inclusion and justice task forces for District of Columbia area cancer centers: Lessons learned implementing efforts in oncology - Katarina E. AuBuchon; Anne McDonnell; Hannah Arem; Teletia Taylor; Yasmine M Kanaan; Marjorie C. Gondré-Lewis; Barbara W. Harrison; Nicole P. Chapell; Julie E. Bauman; Christopher J. King; Pavani Chalasani; Christopher Gallagher; et al. (PLoS ONE, 2026)
Purpose To address observed cancer health inequities resulting from historically-embedded structural bias in quality, equity, and access to health care delivery, we organized and coordinated Diversity, Equity, Inclusion, and Justice (DEIJ) Task Forces across three cancer centers in the Mid-Atlantic region. Methods We recruited multi-disciplinary, diverse faculty and staff for each task force to optimize capacity to implement sustainable, effective strategies for institutional change. We developed an educational curriculum aligned with enhanced National Culturally and Linguistically Appropriate Services (CLAS) Standards and the DC Hospital Health Equity Framework. Over 18 months, task force members were invited to 14 sessions designed to help teams assess and prioritize critical areas for improvement through organizational assessments and then create and implement action plans. Results Task force goals focused on reducing cancer disparities by improving patient information accessibility, expanding the reach of implicit bias training for providers, and improving accurate socio-demographic data collection. The task forces made meaningful progress on two of these three goals. Challenges included competing time demands, incomplete and limited data generated by institutions, limited insight into operational protocols and inadequate resources and time to complete work. Conclusion Clear, accessible patient-reported demographic data, protected staff time, leadership commitment, and significant institutional resource supports are critical to effectively advance DEIJ work.